Reliance in the breaking-off of contractual negotiations : trust and expectation in a comparative perspective / Isabel Zuloaga. - Zuloaga Ríos, Isabel Margarita (Intersentia, 2019)
This book explores the theoretical basis of precontractual liability for the unilateral breaking-off of negotiations from a comparative perspective. It argues that, in the selected civil law jurisdictions (Germany, France and Chile), the true basis of this liability is the notion of 'reliance' and it distinguishes two dimensions of reliance: 'trust-based' and 'expectation-based'. For the selected civil law jurisdictions it can be observed that trust-based reliance merges with the general principle of good faith and that the expectation dimension emanates from the trust-dimension. Therefore, Reliance in the Breaking-Off of Contractual Negotiations argues that this innovative theoretical approach to the foundations of precontractual liability could have important practical consequences in jurisdictions that do not embrace a general principle of good faith, such as English law. If the analysis is shifted from good faith to the notion of reliance, English law could develop a less fragmented approach and encompass cases that are currently devoid of protection. How legal changes could be implemented without establishing a general principle of precontractual liability is explored in the final chapter of the book. In a constantly evolving world where international trade is ever-growing, precontractual liability, particularly for breaking off negotiations, is a topic of constant development by legal scholars and the judiciary and of increasing importance for practitioners, judges and academics, with significant consequences for negotiating contracts both at a national and at a transnational level. DR ISABEL ZULOAGA is Assistant Professor of Commercial Law at Pontificia Universidad Católica de Chile (Santiago, Chile). She has been a Becas Chile Scholar and completed both DPhil and MJur at the University of Oxford, United Kingdom. She is a Member of the British Institute of International and Comparative Law (BIICL), the International Bar Association (IBA) and the Chilean Lawyer's Association (Colegio de Abogados de Chile).